PENGUATAN USAHA JAJANAN TRADISIONAL IBU MISNAH DI DESA GERIMAX INDAH KABUPATEN LOMBOK BARAT - Erviva Fariantin; Indah Ariffianti; Hikmah; Ulfiyani Asdiansyuri; Sukma Hidayat Kurnia Abadi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi AMM, 2026)
Strengthening Ibu Misnah's traditional snack business in Gerimax Indah Village, West Lombok Regency was the topic of a community service activity carried out by lecturers at STIE AMM Mataram. The community service partners were Ibu Misnah's MSMEs, who had been operating for years but lacked legal business registration. Therefore, they needed to understand formal legality as a first step towards the sustainability and success of their business in the future and to be able to compete with other business owners. This was achieved through discussions and mentoring. The results of the community service activity showed that the business owners fully understood the importance of having a Business Identification Number (NIB), a halal certificate, a well-designed label on product packaging, and preparing simple financial reports. They also emphasized the importance of having a precise and clear business location via Google Maps